Portfolio pumping in mutual fund families - Wang, Pingle (Journal of Financial Economics, 2024)
This paper investigates portfolio pumping at the fund family level, where non-star fund managers strategically purchase stocks held by star funds in the family to inflate their quarter-end performance. Star funds that engage in such activities show inflated performance after 2002 when the Securities and Exchange Commission increased regulation on portfolio pumping. Stocks pumped by the strategy show strong reversals at the quarter end. Moreover, despite a minor underperformance stemming from portfolio misallocation, non-star fund managers pumping for star funds receive abnormally high subsequent flows, suggesting a pattern of family subsidization.